Social connectedness in adults with mental disorders: ecological validation of a conceptual framework for novel complex interventions. (4th May 2021) - Hare-Duke, Laurie; Dening, Tom; Oliveira, Déborah; Dewa, Roberta; Slade, Mike
Abstract: Background: Social connectedness interventions may improve the clinical outcomes and personal recovery of adults with mental disorders but many interventions lack a clear theory-base and show limited effectiveness. Aim: To evaluate the validity of a newly developed conceptual framework (the CIVIC framework: Closeness, Identity, Valued relationships, Involvement and Cared for and accepted) to function as the theory-base for novel social connectedness-based mental health interventions. Method: Semi-structured interviews with adults with diagnostically heterogeneous mental disorders (n = 13) and mental health professionals (n = 9). Participants reported their social connectedness experiences, their views on the CIVIC framework and potential targets for new interventions. Sequential inductive and deductive thematic analyses were used. Data quality was assessed through respondent validation. Results: Both inductive and deductive analyses provided validation of the CIVIC framework. Additional themes of Stigma and Connectedness beyond social relationships were identified in the inductive analysis. Candidate interventions to target each CIVIC domain were identified. Conclusions: The CIVIC framework demonstrates ecological validity and can therefore serve as the theory-base for the development of novel social connectedness-based interventions. This study indicates that interventions would be most effective when they incorporate evidence-based approaches which target each of the categories described by the CIVIC framework.